Cells as delivery vehicles for cancer therapeutics - Basel, Matthew T.; Shrestha, Tej Bahadur; Bossmann, Stefan H.; Troyer, Deryl L. (My University, 2014)
Cell-based therapeutics have advanced significantly over the past decade and are poised to become a major pillar of modern medicine. Three cell types in particular have been studied in detail for their ability to home to tumors and to deliver a variety of different payloads. Neural stem cells, mesenchymal stem cells and monocytes have each been shown to have great potential as future delivery systems for cancer therapy. A variety of other cell types have also been studied. These results demonstrate that the field of cell-based therapeutics will only continue to grow.
Keywords: Tumor tropism; Chemotaxis; Magnetic hyperthermia; Cell‐based gene therapy; Suicide gene; Cancer therapies